2007
DOI: 10.1074/jbc.m704434200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of NFκB Activity and E-cadherin by the Type III Transforming Growth Factor β Receptor Regulates Cell Growth and Motility

Abstract: Transforming growth factor ␤ is growth-inhibitory in nontransformed epithelial cells but becomes growth-promoting during tumorigenesis. The role of the type I and II receptors in tumorigenesis has been extensively studied, but the role of the ubiquitously expressed type III receptor (T␤RIII) remains elusive. We developed short hairpin RNAs directed against T␤RIII to investigate the role of this receptor in breast cancer tumorigenesis. Nontumorigenic NMuMG mouse cells stably expressing short hairpin RNA specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 48 publications
4
33
0
Order By: Relevance
“…In addition, although induction of myr-Akt was also found to activate p65-dependent transcription, probably through repression of IB␣ expression, 33 we failed to confirm such an association in tumor tissues, suggesting that the in vivo pp65 status may be affected not only by pAkt but also by other factors, such as transforming growth factor-␤ and tumor necrosis factor-␣. 34,35 In our results, expression of Slug, rather than Snail, appeared to be closely associated with the mesenchymal phenotype in UCSs, despite both being capable of repressing E-cadherin expression. 12,13 A similar finding has also been reported for basal-like breast carcinomas.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, although induction of myr-Akt was also found to activate p65-dependent transcription, probably through repression of IB␣ expression, 33 we failed to confirm such an association in tumor tissues, suggesting that the in vivo pp65 status may be affected not only by pAkt but also by other factors, such as transforming growth factor-␤ and tumor necrosis factor-␣. 34,35 In our results, expression of Slug, rather than Snail, appeared to be closely associated with the mesenchymal phenotype in UCSs, despite both being capable of repressing E-cadherin expression. 12,13 A similar finding has also been reported for basal-like breast carcinomas.…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, a recent report using cDNA microarrays showed that decreased ThRIII expression correlated with higher tumor grade in a cohort of breast cancers (4). Our laboratory has recently published data supporting a tumor suppressor role for ThRIII in nontumorigenic NMuMG mammary epithelial cells that is dependent on the ability of ThRIII to modulate nuclear factor-nB (NF-nB) signaling (6). In contrast, an oncogenic role for ThRIII was suggested by studies in lymphoma, B-chronic lymphocytic leukemia, and certain ovarian tumors (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…All cells were maintained in a humidified 5% CO 2 incubator at 37jC. Retroviruses expressing shRNAs specific to mouse or human ThRIII were generated as previously described (6). Retrovirus containing mouse or human sh-RIII were used to infect MDA-231 and PMTLuc cells in the presence of 4 Ag/mL polybrene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TβRIII has been shown to have effects on both the Smad and non-Smad signaling pathways in a liganddependent or -independent manner, including the Smad, NF-κB and p38 signaling pathways (33)(34)(35). In mouse lung fibroblasts, the expression of TβRIII was found to reduce the phosphorylation of Smad2, Smad3 and Akt (36).…”
Section: Discussionmentioning
confidence: 94%